Análisis de las contrataciones por procedimientos de selección en la Municipalidad Provincial De Maynas período 2018-2022 - Rodriguez Isuiza, Katterine Marbella (2024)
Provincial municipalities promote local development, seeking to facilitate local competitiveness and promote the best living conditions for their population. The purpose of this thesis is to describe hiring through selection procedures in the provincial municipality of Maynas, during the period 2018-2022, for which a descriptive scope, quantitative in nature and non-experimental design was used, analyzing the types of procedures selection procedures established in the state procurement regulations, as well as the contracting objects required by the entity. Taking into account the results, it is determined that the contracts of the Provincial Municipality of Maynas by type of selection procedure, during the analysis period, reached a total awarded amount of S/ 204,750,655.23 million, with the “Public Bidding” procedure being the which recorded the highest amount awarded for S/ 96,481,622.69 million, representing 47.12% of the total, followed by “Simplified Award” with an amount of S/ 62,511,443.31, which represents 30.53% of the total and in third place is “Direct Contracting”. ” with an amount of S/ 27,714,856.36, which represents 13.54% of the total awarded; destined mainly for the purchase of goods, with 59 procedures awarded during the five-year period analyzed.